A comparison of the differences in the way parents and grandparents interact with children and their effects on children’s creative performance - Lu, Ye; Pei, Yilai; Pang, Weiguo (Frontiers in Psychology, 2022)
As grandparents’ involvement in parenting becomes more common, it is valuable to understand the differences between grandparenting and parenting and how these differences affect children. To elucidate the differences between grandparenting and parenting and their effects on children’s creativity performance, children’s performance on creativity tasks after grandparent–child interactions and parent–child interactions were compared, and the behavioral differences between grandparents and parents when interacting with children were discussed. In this study, grandparents and parents were asked to interact with children separately, and creativity performance was measured before and after adult-child interactions. The results showed that children’s creative performance improved significantly after parent–child interactions, while there was little change after grandparent–child interactions. In addition, according to parental investment theory, parents provided children with more cognitive and interpersonal resources during the interaction compared to grandparents.